Khader’s minimalist, pluralist universalism - Alcoff, Linda Martín (Journal of global ethics, 2020)
Serene Khader’s effort to develop a decolonized approach to transnational feminism takes a helpfully nonideal approach. Much of decolonial theory has criticized universalism in order to espouse pluralism. Khader attempts to develop a form of minimalist universalism compatible with a significant dose of pluralism in regard to how we understand liberation from gender-based forms of oppression, and she effectively shows how the nonideal, meliorative approach can do this. I address three issues here: (1) the serious challenge her universalist account poses to critical theory and some other trends in continental philosophy; (2) the persuasive analysis of, approach to, and critique that she makes of ‘gender role eliminativism’ and (3) the epistemic and dialogic questions left remaining in her defense of feminist universalism, in relation to who can theoretically formulate the universal.